UPAYA GURU IPS DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL PESERTA DIDIK PADA PEMBELAJARAN IPS DI SMP NEGERI 33 SEMARANG - Nisriyana, Diyah; Hermanto, Fredy (Sosiolium: Jurnal Pembelajaran IPS, 2023)
Teachers have a big share in developing students' social skills through learning in the classroom because teachers act as learning designers, managers, and assessors of student. The importance of students' social skills in social science learning requires the teacher to make efforts that focus on developing students' social skills in order to realise the objectives of social science learning. Therefore, this study discusses the efforts of the teacher in developing students' social skills in social science learning including the process of developing social skills and inhibiting factors in developing social skills at SMP Negeri 33 Semarang. Data collection techniques using observation, interviews, and documentation. The results of this study are: (1) The efforts made by social science teachers in developing social skills of students in the aspect of peer relations, academic behavior, and self management is done on the implementation of social science learning that include preliminary, core, closing activities. (2) The obstacles faced by social science teachers including: lack of concern for students, students are not fully focused on the materials, minimal support facilities, and lack of responsibility of students in completing tasks. Guru memiliki andil yang besar dalam mengembangkan keterampilan sosial melalui pembelajaran di kelas karena guru berperan sebagai perancang, pengelola, dan evaluator. Pentingnya keterampilan sosial siswa pada pembelajaran IPS mengharuskan guru IPS melakukan upaya pengembangan keterampilan sosial demi mewujudkan tujuan pembelajaran IPS. Oleh karena itu, penelitian ini membahas tentang upaya guru IPS dalam mengembangkan keterampilan sosial siswa pada pembelajaran IPS meliputi proses pengembangan keterampilan sosial dan faktor penghambat pengembangan keterampilan sosial di SMP Negeri 33 Semarang. Pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil dari penelitian ini adalah: (1) Upaya yang dilakukan guru IPS dalam mengembangkan keterampilan sosial siswa pada aspek hubungan teman sebaya, keterampilan akademik, dan manajemen diri yang dilakukan pada pelaksanaan pembelajaran IPS yang meliputi kegiatan pendahuluan, inti, dan penutup. (2) Adapun kendala yang dihadapi guru IPS, diantaranya yaitu: kurangnya kepedulian siswa, siswa belum sepenuhnya fokus pada materi, kurangnya fasilitas penunjang belajar, serta kurangnya tanggung jawab siswa dalam menyelesaikan tugas.